Strategi Pengembangan Agrowisata terhadap Peningkatan Pariwisata Berkelanjutan di Desa Jaranguda - Aisyah Aisyah; Anugrah Permana Tanjung; Ade Aulia Riski; Geri Bintang Rikardi; Nurwani Nurwani (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2026)
The low utilization of agrotourism potential in Karo Regency, particularly in Jaranguda Village, indicates the need for a well-planned and integrated development strategy to optimize the synergy between the agricultural and tourism sectors in a sustainable manner. Although this village possesses abundant natural resources, attractive landscapes, and extensive as well as productive agricultural land, the local community still heavily relies on conventional farming practices. This dependence results in relatively unstable economic conditions and limits the community’s ability to adapt to changing demands in the tourism market. This study aims to analyze the development of agrotourism as a strategic effort to enhance sustainable tourism in Jaranguda Village. The research method employs a descriptive qualitative approach, with data collected through field observations, in-depth interviews with community members and key stakeholders, and a review of relevant literature. The findings indicate that agrotourism development requires strong and continuous collaboration among local communities, local government, and tourism-related business actors. The recommended development strategies include improving community capacity and skills, strengthening digital promotion based on local potential, enhancing supporting infrastructure for agrotourism, and implementing the principles of sustainable tourism. The implementation of these strategies is expected to strengthen the village economy, create new employment opportunities, and enhance the regional tourism competitiveness in a sustainable manner.